2015
DOI: 10.1111/1462-2920.13072
|View full text |Cite
|
Sign up to set email alerts
|

Environmental roles of microbial amino acid racemases

Abstract: SummaryEnzymes catalysing the stereo-chemical interconversion of amino acids are known as amino acid racemases. In bacteria, these enzymes are fundamental to synthesize the D-Ala and D-Glu that are critical components of the peptidoglycan. In addition to this structural function in cell wall assembly, D-amino acids produced by microbial amino acid racemases have been described as relevant constituents in other prokaryotic structures (e.g. capsule, non-ribosomal peptides) and have been associated to growth fitn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 165 publications
0
47
0
1
Order By: Relevance
“…Microorganisms may also rebuild proteins directly from the necromass amino acids 29 . For this, D-amino acids need to be converted into L-forms by racemases 30 . The continuous reworking of the necromass pool pulls the sedimentary D:L-Asp ratio away from the equilibrium ratio that would otherwise result from pure abiotic racemization (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms may also rebuild proteins directly from the necromass amino acids 29 . For this, D-amino acids need to be converted into L-forms by racemases 30 . The continuous reworking of the necromass pool pulls the sedimentary D:L-Asp ratio away from the equilibrium ratio that would otherwise result from pure abiotic racemization (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…D-alanine is also released from the teichoic acids by spontaneous hydrolysis (16), consequently there should be an accumulation of free D-alanine residues in the vicinity of a growing cell unless actively re-assimilated by the bacterial cells. Pervious analyses of culture media composition after the growth of various bacterial species have revealed that many release D-amino acids on reaching stationary phase growth, presumably as secondary metabolites or signalling molecules (2). Indeed, stationary phase cultures of S. aureus have been shown to have significant levels of D-alanine present (1).…”
Section: Introductionmentioning
confidence: 99%
“…Lysine decarboxylase is one of the PLP-dependent enzymes [5][6][7]. Therefore, the effect of PLP concentration in the reaction medium was examined.…”
Section: Characterization Of the Recombinant Lysine Decarboxylasementioning
confidence: 99%